Historicity of Aisyiyah’s Da’wa: A Study of Aisyiyah Da’wa Movement from Sopo Tresno (1914) Until Aisyiyah (2010) from an Aqidah Perspective - Imroatul Istiqomah (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2024)
The Islamic community experienced a crisis at the beginning of the 20th century. The condition of women at that time was very concerning. Women were regarded as Konco Wingking (a term referring to those responsible for household chores), a position that had evolved into an ingrained cultural ideology contributing to women's ignorance and backwardness. This issue was of great importance to Nyai Ahmad Dahlan and her husband, prompting them to initiate the establishment of an internaat (boarding school) to support Indonesian girls. This study examines the history of the Sopo Tresno and Aisyiyah da'wah movements. It is a literature-based research drawing primary sources from books, conference proceedings, and scholarly works. The approach used is descriptive-analytical, with data validity tested using measures of transferability and reliability. The analysis method employed is inductive. The results will establish the foundation of Aisyiyah's da'wah from Sopo Tresno (1914) to Aisyiyah in 2010 from the perspective of aqidah.